Analisis Pengaruh Fixed Carbon terhadap Kehilangan Massa Batubara pada Tambang Air Laya Menggunakan Model Tungku Pembakaran Sederhana di PT Bukit Asam Tbk - Debby Meiza Asridza; Maulana Yusuf; Restu Juniah (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Coal storage in stockpiles is prone to spontaneous combustion, which can cause mass loss, declining energy quality, and potential fire hazards. This phenomenon not only poses occupational safety risks but also causes significant economic losses due to coal mass loss and reduced calorific value. This study used a quantitative descriptive method as an instrument to produce a systematic, evidence-based description of the coal spontaneous combustion phenomenon, and to evaluate the effect of fixed carbon on changes in coal mass before and after burning. The samples used had calorific values of ±4.200 Kcal/Kg, ±4.900 Kcal/Kg, ±5.300 Kcal/Kg, and ±7.100 Kcal/Kg, with kerosene used as an initial trigger in the combustion process, allowing the spontaneous combustion phenomenon to be simulated and observed under controlled conditions. The artificial spontaneous combustion process lasted 6 hours, with temperature measurements taken every 30 minutes. The results showed that coal with a low calorific value (±4.200 Kcal/Kg) had the lowest average fixed carbon content, at 39,86%, and this value increased progressively with increasing calorific value. The higher the proportion of fixed carbon in the coal composition, the lower the mass loss, a pattern systematically confirmed across the entire research dataset. Regular temperature monitoring should be routinely conducted on coal stockpiles, particularly during the first 90 minutes of storage, as this period exhibits the most significant temperature increase.